Formulation and Evaluation of Oral Disintegrating Film Containing Lisinopril for the Effective Management of Hypertension and Cardiac Diseases - Velayutham Pazhanivel (Journal of Global Pharma Technology, 2020)
This study was aimed to develop oral disintegrating film (ODF) containing an anti-hypertensive drug Lisinopril. Five trial formulations (F1-F5) of Lisinopril ODF were prepared using Hydroxypropyl methylcellulose E15 (HPMCE15), Polyvinyl pyrrolidone (PVPK30), Polyethyleneglycol400, Polyplasdonexl, Mannitol, Peppermint oil, Propylparaben, Citric acid, and Allura red. The prepared formulations were evaluated for their Physico-chemical characters like weight, thickness, surface pH, folding endurance, and disintegration time. They were also evaluated for the content of Lisinopril. The above studies revealed that formulations trial F4 was better than other Formulations. Because, it has exhibited faster disintegration time (21.32 sec) when compared to the other formulation. So, F4 was selected for stability study (40ᵒC,75% RH) for six months and Scanning Electron Microscopy (SEM). The results of the above studies have shown that F4 was stable and has a uniform distribution of Lisinopril.